Spain : index to summary of decisions adopted by the British Trade Union and Labour movement and the International Federation of Trade Unions and the Labour and Socialist International - International Federation of Trade Unions ; Labour and Socialist International
1938 017b-0031-002 292/946/17b/37(ii)